1982
DOI: 10.1017/s0022112082000378
|View full text |Cite
|
Sign up to set email alerts
|

The vortex-shedding process behind two-dimensional bluff bodies

Abstract: Using a variety of flow-visualization techniques, the flow behind a circular cylinder has been studied. The results obtained have provided a new insight into the vortex-shedding process. Using time-exposure photography of the motion of aluminium particles, a sequence of instantaneous streamline patterns of the flow behind a cylinder has been obtained. These streamline patterns show that during the starting flow the cavity behind the cylinder is closed. However, once the vortex-shedding process begins, this so-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
106
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(121 citation statements)
references
References 3 publications
15
106
0
Order By: Relevance
“…The vortex formation is characterized by the shear layer from the other side of the wake cutting off the vorticity supply to the growing vortex from the cylinder wall, just as stated by Gerrard. 21 From a flow topology, the birth of a new vortex is associated with the formation of a saddle point, as earlier found by Perry et al 23 For Riϭ1.0, it is observed that pairs of counterrotating vortices appear directly behind the cylinder. The distance between the counterrotating vortices is exactly the same as the distance between the plumes, being twice the cylinder diameter.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The vortex formation is characterized by the shear layer from the other side of the wake cutting off the vorticity supply to the growing vortex from the cylinder wall, just as stated by Gerrard. 21 From a flow topology, the birth of a new vortex is associated with the formation of a saddle point, as earlier found by Perry et al 23 For Riϭ1.0, it is observed that pairs of counterrotating vortices appear directly behind the cylinder. The distance between the counterrotating vortices is exactly the same as the distance between the plumes, being twice the cylinder diameter.…”
Section: Discussionsupporting
confidence: 60%
“…5͑b͒ to 5͑c͒, the N2͑AL͒ cuts off the vorticity supply of the vortex B from the cylinder wall. The hypothesis of Perry et al 23 has been reconfirmed that the birth of a new vortex is characterized by the formation of a new saddle point in the streamline topology.…”
Section: Unheated Case: Vortex Formationmentioning
confidence: 94%
See 2 more Smart Citations
“…For unsteady flows time can also be considered a parameter in the system (1). A general bifurcation theory for streamline patterns has been developed by several authors [28,29,30,31,32,33] and many applications to specific flow problems such as vortex breakdown [34,35], driven cavities [36,37,38], the cylinder wake [39,40] and peristaltic flows [41] are available. The analysis of topological bifurcations consists in identifying degenerate streamline patterns and their unfoldings, that is, parametrized families of velocity fields which can represent all possible perturbations of the given degenerate pattern.…”
Section: Introductionmentioning
confidence: 99%